ONLINE LEARNING DURING THE COVID 19 PANDEMIC THROUGH THE PRODUCTION BASED TRAINING (PBT) MODEL ASSISTED WITH YOUTUBE MEDIA ANIMATION MATERIALS IN CLASS XI MM 2 SMK NEGERI 1 MOJOANYAR (BEST PRACTICE) - Ivan Suseno (Jurnal Scientia, 2022)
21st century skills which include problem solving, critical thinking, collaboration and communication are important as students enter the workforce. This article is a report from best practice with the aim of providing a description of the implementation of learning by applying the production based training (PBT) model with the help of youtube media. This article is a best practice report so that the method of writing / research uses a one shot case study involving 34 students of class XI MM 1 SMK Negeri 1 Mojoanyar. The learning material is 2D animation technique. The implementation of this best practice is in August - September 2020. The data collection technique uses a questionnaire, the data analysis technique uses descriptive quantitative. The results of the study show that online learning by applying the production based training (PBT) model with YouTube media can increase students' motivation and learning outcomes. Students gave a positive response to the application of the model and the completeness of classical learning outcomes reached 88.24%.